Aboriginal/Anglo Relations as Portrayed in the Folklore of Micmac ‘Witching’ in Newfoundland - Rieti, Barbara (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1995)
This article examines the social implications of the tradition found in certain parts of Newfoundland that an offended “Indian” can put a “wish” or “spell” on the offender. Narratives typically involve itinerant native basketsellers from Nova Scotia, but have been recorded in connection with Micmac residents of the south coast as well; there is also a group of non-narrative reports about alleged Micmac methods of getting magic power. A full analysis of this material must set it in relation to the larger body of Newfoundland witch lore, but, as a subset with distinctive features, the idea of “Indian curses” poses many questions about native/European interaction. Did it foster fair (if guarded) relations, or hostility - or both ? Did it have a basis in Micmac culture, and did the Micmacs use it, or is it purely a folklore of “otherness.”